Role of DNA methylation in ecophysiological responses to salinity in natural populations of Phragmites australis from coastal and inland habitats - Song, Huijia; Guo, Xiao; Liu, Lele; Xu, Zhenwei; Wang, Ning; Liu, Xiao; Du, Ning; Guo, Weihua (Frontiers in Marine Science, 2022)
There are different environmental pressures in coastal and inland wetlands resulting in phenotypic variation among plant populations, which might be related to epigenetic modifications. Phragmites australis is a widespread plant in coastal and inland wetlands, and the phenotype of the population is selected by salinity, but the reasons for the population differences in salt tolerance and phenotype are unclear. We investigated coastal and inland P. australis populations grown under two salinities and two manipulated DNA methylation levels in common gardens. The plants were sprayed with 5-azacytidine (DNA demethylation agent) regularly, and the physiological and morphological traits of reeds were measured. Plant height, density, and basal stem of reeds from different sources were significantly different and correlated with soil conductivity of sampling sites (P < 0.05). Salinity significantly decreased the biomass (37.04%, P < 0.05) and plant height (24.68%, P < 0.05) of inland reeds but had no significant effect on coastal populations (13.48%). P. australis responds to salt stress through phenotypic plasticity, and inland wetland populations exhibit local adaptation to freshwater. Increased salt tolerance in inland populations following DNA demethylation, particularly biomass, plant height, and basal stems (increased 23.62%; 13.08%; 5.35%, respectively), could provide more opportunities in adverse environments. This study will provide important insights into the highly adaptive mechanisms of the large non-model plant.